2017
DOI: 10.3892/mmr.2017.7886
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑27a promotes tumorigenesis via targeting AKT in triple negative breast cancer

Abstract: Altered microRNA (miRNA/miR) expression regulates tumor development and progression in triple‑negative breast cancer (TNBC). The present study examined the effect of miR‑27a on proliferation, migration and invasion of TNBC cells in vitro and in vivo. An MTT assay was performed to examine the proliferation of MDA‑MB‑231 and MDA‑MB‑468 breast cancer cells with either overexpression of miR‑27a or downregulation of miR‑27a, in the presence or absence of radiation. The migratory and invasive abilities of MDA‑MB‑231… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…4c). Conversely, the expression of PTEN, an inhibitor of PIK3/AKT signalling, increased in miR-27a_KD cells while diminished in miR-27a_OE cells with respect to their controls, consistent with PTEN being a direct target of miR-27a 40 (Fig. 4c).…”
Section: P-ampk/ampk Ratio Increased While the P-mtor/mtor Ratio Sligsupporting
confidence: 70%
See 2 more Smart Citations
“…4c). Conversely, the expression of PTEN, an inhibitor of PIK3/AKT signalling, increased in miR-27a_KD cells while diminished in miR-27a_OE cells with respect to their controls, consistent with PTEN being a direct target of miR-27a 40 (Fig. 4c).…”
Section: P-ampk/ampk Ratio Increased While the P-mtor/mtor Ratio Sligsupporting
confidence: 70%
“…In cancer cells, mTOR can be regulated by the mitogenresponsive signalling, such as PI3K/AKT which contributes to tumorigenesis and chemoresistance. 14,39,40 Interestingly, we found that AKT phosphorylation was reduced in HCT116 and SW480 miR-27a_KD cells while increased in HT29 miR-27_OE (Fig. 4c).…”
Section: P-ampk/ampk Ratio Increased While the P-mtor/mtor Ratio Sligmentioning
confidence: 79%
See 1 more Smart Citation
“…Comparison of the lists of highly expressed miRNAs identified in analyzed cells revealed seven molecules, whose oncogenic properties were already associated with this cancer type, that may represent a novel molecular biomarkers or therapeutic targets for treatment of this disease. Indeed, cell viability and epithelial-mesenchymal transition-promoting properties of miR-221-3p were already described, together with its ability to induce cell proliferation of TNBC cells [73], a characteristic feature known also for another four highly expressed miRNAs: miR-181b-5p, miR-21-3p, miR-25-3p, and miR-27a-3p [44,47,74,75]. Moreover, highly expressed miRNAs miR-103-3p, miR-181b-5p, miR-20a-5p, miR-21a-3p, miR-221-3p, and miR-27a-3p are involved in regulation of TNBC cells migration [44][45][46][73][74][75], whereas miR-103-3p, miR-20a-5p, and miR-27a-3p have been previously associated with invasion of TNBC cells [45,46,75].…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, expression of miR-181b-5p represents a common feature of aggressive breast cancers [74], whereas another two miRNAs-miR-103-3p and miR-20a-5p-were found to be highly expressed in both TNBC tissues and cell lines [45,46]. Finally, it was demonstrated that overexpression of miR-27a-3p and miR-181b-5p confers chemoresistance to PARP (poly ADP ribose polymerase) inhibitors [39] and neutralizes the ionizing radiation effect [43,75], respectively. Altogether, these data indicate that the sncRNA expression dataset generated here represents a valuable source of information for further evaluation of potential of aforementioned miRNAs and other molecules as molecular biomarkers of TNBC.…”
Section: Discussionmentioning
confidence: 99%